Numerical Solution of Dirichlet Boundary Domain Integro Differential Equation with Less Number of Collocation Points - Nurul Akmal Mohamed; Nurul Farihan Mohamed; Nurul Huda Mohamed; Mohd Rozni Md Yusof (Hikari LTD., 2024)
Indexed by Scopus